Association of the IL-10 and IL-18 polymorphisms with nasopharyngeal carcinoma risk - Chen, Xueru; Zhang, Ruibin; Xie, Hui; Li, Sha; Guo, Jincai; Wang, Yan (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the possible association of the cytokine polymorphisms with the risk of nasopharyngeal carcinoma (NPC).MethodsWe performed a comprehensive search of electronic databases from PubMed, Web of Science, Embase, and CNKI. Articles related to the cytokine polymorphisms in patients with NPC and healthy controls from inception to 1 April 2024 were included. The results were analysed independently by two reviewers using RevMan 5.4 software. Summary odds ratio (OR) and 95% confidence interval (CI) were used to evaluate cancer risk.ResultsOur results showed that IL-10 1082A>G showed a significant difference only in the Dominant model, but in the Asian population, a significant difference was shown in all models. IL-18 607C>A polymorphism showed significant differences in the Allele model, Heterozygote model, and Homozygote model. In addition, the IL-18 137G>C polymorphism showed significant differences in all models. No statistically significant association was found between IL-8 251A>T, IL-10 819T>C polymorphism, and the risk of NPC.ConclusionOur meta-analysis results suggest that the IL-18 607C>A and IL-18 137G>C polymorphism are associated with the increased risk of NPC, and IL-10-1082 A/G polymorphism is associated with the increased risk of NPC in Asian populations.